2020
DOI: 10.3389/fneur.2020.00180
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Supranuclear Palsy—Parkinsonism Predominant (PSP-P)—A Clinical Challenge at the Boundaries of PSP and Parkinson's Disease (PD)

Abstract: Progressive Supranuclear Palsy (PSP) and Parkinson's Disease (PD), especially in their early stages, show overlapping clinical manifestations. The criteria for the diagnosis of PSP, released in 2017, indicate four basic features of the disease-postural instability (P), akinesia (A), oculomotor dysfunction (O) and cognitive and lingual disorders (C), which clarify the interpretation of the disease. There is growing interest in the second most common variant of PSP-parkinsonism predominant PSP-P. It is observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 48 publications
(45 reference statements)
3
61
0
1
Order By: Relevance
“…Patients with PSP have a reduced FDC in both the corona radiata and internal capsules. Such alterations are in line with the higher severity of motor deficits observed in patients with PSP than in those with PD (Alster et al, 2020 ).…”
Section: Discussionsupporting
confidence: 65%
“…Patients with PSP have a reduced FDC in both the corona radiata and internal capsules. Such alterations are in line with the higher severity of motor deficits observed in patients with PSP than in those with PD (Alster et al, 2020 ).…”
Section: Discussionsupporting
confidence: 65%
“…This study, therefore, reports primarily on PSP-RS, not other subtypes of PSP, and is likely an underestimation of the prevalence of all types of PSP. However, some of the patients in this study may also have PSP-P, which is the second most common variant of PSP and observed in up to 35% of cases ( 30 ). In the only epidemiologic study including PSP subtypes other than PSP-RS, conducted in Japan, the prevalence of PSP-RS only was 13.8 per 100,000, while the prevalence of all PSP was higher at 17.3 per 100,000 ( 21 ).…”
Section: Discussionmentioning
confidence: 75%
“…MSA patients had increased 3 rd V width, which is in accordance with a volumetric MRI study [12] reporting larger ventricular system (including lateral, third and fourth ventricles) in MSA and PSP compared to PD patients. In our CUP-cohort, diagnostic accuracy was better for PSP-RS than for PSP-P, most probably because PSP-P is associated with a less severe course of the disease and less severe atrophy of infratentorial brain structures [10] pathognomonic for PSP as assessed with MR planimetry.…”
Section: Discussionmentioning
confidence: 80%